Demographic study: Aging in the context of urban decline in Vojvodina cities - Pogrmić Zorica; Bubalo-Živković Milka; Đerčan Bojan; Sekulić Milena (Glasnik Srpskog Geografskog Društva)
This paper analyses the aging of the population in AP Vojvodina (Serbia) in the period from 2002 to 2022, with a focus on eight cities. The results reveal complex dynamics related to urban decline and population aging. In this period, although the share of the urban population in the total population of Vojvodina increased by 5.1 percentage points, the number of residents in urban areas decreased by 6.2%. That indicates significant regional variations within Vojvodina, with some cities recording a noticeable decrease in inhabitants. Analysing the demographic factors that contribute to the decline of cities, the research observes an increase in elderly, the median age and the old dependency ratio. We focus on the accelerated increase in the share of elderly (65 and over) (2011-2022). This trend has significant implications for the economic structure, social resources and the health sector, given the needs of the elderly population for health care and support. The research emphasizes the importance of looking at the demographic dynamics and the process of population aging and the necessity of creating adequate policies to face the challenge of declining cities in Vojvodina.